Green Calcium Ammonium Phosphate (CAP) Fertilizer Synthesis from Red Mussel Shells (Anadara granosa): An Optimization Study Using Response Surface Methodology - Raka Selaksa Charisma Muchammad; Ketut Sumada (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study investigates the synthesis of Green Calcium Ammonium Phosphate (CAP) fertilizer utilizing red mussel shells (Anadara granosa) as a biogenic precursor. Response Surface Methodology (RSM) was employed to optimize process variables, identifying an optimal operating window at pH 8.000 and a feed-to-phosphoric acid ratio of 0.100 (w/v). Under these conditions, the model predicted a Phosphorus concentration of 25.647%, Calcium content of 71.861%, and a Yield of 77.621 (desirability: 0.628). However, ANOVA diagnostics revealed a significant Lack of Fit, suggesting that standard quadratic models are sensitive to latent physicochemical parameters inherent in the biogenic matrix. These statistical discrepancies indicate that while successful at the laboratory scale, current predictive frameworks require kinetic refinement prior to large-scale industrial implementation. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action